Present and Consistent God in Creation, in the Look of the Qur'an and Argument - Mohammad Bagher Saeidi Roshan (آموزه‌های قرآنی, 2019)
Field. The issue of the continual need for God in the universe, and the necessity of the subjective presence of God and the role of God in the work of the universe after creation, is one of the fundamental issues of theology. Goal. This study attempts to investigate this issue in the light of Qur'anic verses and rational intellectual analysis. Method. The method used in this study is the application of rational analysis, interpretation and discourse analysis of the Qur'anic descriptions of the role and subjective presence of God in the world and the world’s constant need for God. Findings. According to the Qur'an’s description of God’s relationship with the world, in line with the rational analysis of Muslim scholars of the inherent possibility and the existential need of creatures, the universe is not a historical occurrence; rather, the universe is in constant need of reliance on the subsistent God. Result. The God of the Qur'an has always been present in the context of the world, and the universe and its individual are constantly in occurrence and new transformation and always in need of God.